Effect of nitrogen application on enhancing high-temperature stress tolerance of tomato plants during the flowering and fruiting stage - Luo, Jing; Yang, Zaiqiang; Zhang, Fengyin; Li, Chunying (Frontiers in Plant Science, 2023)
This study was conducted to investigate the effects of nitrogen application on growth, photosynthetic performance, nitrogen metabolism activities, and fruit quality of tomato plants under high-temperature (HT) stress. Three levels of daily minimum/daily maximum temperature were adopted during the flowering and fruiting stage, namely control (CK; 18°C/28°C), sub-high temperature (SHT; 25°C/35°C), and high-temperature (HT; 30°C/40°C) stress. The levels of nitrogen (urea, 46% N) were set as 0 (N1), 125 (N2), 187.5 (N3), 250 (N4), and 312.5 (N5) kg hm2, respectively, and the duration lasted for 5 days (short-term). HT stress inhibited the growth, yield, and fruit quality of tomato plants. Interestingly, short-term SHT stress improved growth and yield via higher photosynthetic efficiency and nitrogen metabolism whereas fruit quality was reduced. Appropriate nitrogen application can enhance the high-temperature stress tolerance of tomato plants. The maximum net photosynthetic rate (PNmax), stomatal conductance (gs), stomatal limit value (LS), water-use efficiency (WUE), nitrate reductase (NR), glutamine synthetase (GS), soluble protein, and free amino acids were the highest in N3, N3, and N2, respectively, for CK, SHT, and HT stress, whereas carbon dioxide concentration (Ci), was the lowest. In addition, maximum SPAD value, plant morphology, yield, Vitamin C, soluble sugar, lycopene, and soluble solids occurred at N3-N4, N3-N4, and N2-N3, respectively, for CK, SHT, and HT stress. Based on the principal component analysis and comprehensive evaluation, we found that the optimum nitrogen application for tomato growth, yield, and fruit quality was 230.23 kg hm2 (N3-N4), 230.02 kg hm2 (N3-N4), and 115.32 kg hm2 (N2), respectively, at CK, SHT, and HT stress. Results revealed that the high yield and good fruit quality of tomato plants at high temperatures can be maintained by higher photosynthesis, nitrogen efficiency, and nutrients with moderate nitrogen.